Evaluation of Mean Change in Serum PSA Levels and Renal Function Parameters Following Urological Procedures in Benign Prostatic Hyperplasia Patients - Muhammad Waqas, Haroon Israr, Shoaib Rasul, Raheel Sheikh, Ahmed Sajjad, Mahvesh Mahmud (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms in aging males, often leading to elevated serum PSA levels and impaired renal function. Surgical intervention is the mainstay of treatment in symptomatic cases not responding to medical therapy. Objectives: To evaluate the mean changes in serum prostate-specific antigen (PSA) levels and renal function parameters—serum creatinine and estimated glomerular filtration rate (eGFR)—before and after various urological procedures in patients with BPH. Study Design & Setting: This observational analytical study was conducted at the Department of Urology at Kidney Centre, Bahawal Victoria Hospital, Bahawalpur over a period of 6 months from January 2023 to June 2023. Methodology: A total of 120 male patients diagnosed with BPH and scheduled for surgical intervention were enrolled. Patients underwent either Transurethral Resection of the Prostate (TURP), Holmium Laser Enucleation of the Prostate (HoLEP), or Open Prostatectomy. Pre- and post-procedural serum PSA, serum creatinine, and eGFR were recorded and analyzed using paired t-tests and one-way ANOVA. Results: All three procedures resulted in significant reductions in serum PSA and creatinine levels and significant increases in eGFR (p < 0.001). The greatest PSA decline was seen with open prostatectomy (-5.9 ± 2.3 ng/mL). Changes in renal function parameters were comparable among groups (p > 0.05), indicating overall renal function improvement irrespective of procedure type. Practical Implication: Surgical treatment of BPH not only alleviates obstructive symptoms but also contributes to measurable improvements in renal function and PSA normalization, thereby supporting timely intervention. Conclusion: Urological procedures for BPH significantly reduce PSA levels and improve renal function parameters, with all three methods proving effective in the postoperative restoration of urinary and renal health. Keywords: benign prostatic hyperplasia, creatinine, eGFR, HoLEP, open prostatectomy, PSA, TURP